Some integral inequalities involving Mittag–Leffler functions for tgs‐convex functions. Issue 5 (27th May 2021) - Farid, Ghulam; Zahra, Moquddsa
Abstract: In this article we give some integral inequalities for tgs ‐convex functions which provide refinements of well‐known integral inequalities for unified integral operators. Consequently, various results for convex functions are compared. Furthermore, applications are studied by considering the particular functions to get results for fractional integral operators.